Expansion Collapse Theory of Cosmological Evolution - ZHANG Shao-yong (Journal of Harbin University of Science and Technology)
In the big bang theory，many key puzzles have not been solved． This paper presents an expansion collapse theory of cosmological evolution that the universe originated from the big bang，expanding at beginning， then contracting，and finally collapsing to the origin of the big bang． Some answers are given to the formation of the big bang，the triggering mechanism of the big bang，the accelerating expansion of universe，dark energy and gravitational waves．